The Impact of Inventories on the Leanness of Job Shop Production System - Dawood, Lamyaa Mohammed; Khudair, Anat Amer (Anbar Journal of Engineering Sciences, 2019)
Lean is a powerful process improvement strategy that is widely used to improve different processes. In this Paper, lean manufacturing as process improvement strategy is employed throughout relative tools and techniques as VSM, 5S, and standard work. These tools and techniques are employed to identify measure and evaluate processes. Job shop production of General Company for hydraulic industries, with focus on Damper and Tasks Factory (DTF) is tested as a case study for the two most customer demanded rear dampers of Samaned and Nissan. Data analysis shows different issues Work-In-Process (WIP) issues causing under/ over and production discrepancy. Improvements are introduced throughout WIP developments and 5S techniques. Results show that these developments may result in reduction of 65% WIP waiting time for Nissan and 58% of Samaned rear dampers. An increase in Overall Work Efficiency (OWE) could result in by 10% for Nissan, and 2% for Samaned dampers While 5S may result in improvements by 50% production processes and 43% assembly processes for Set in order , and by 33% in both production and assembly processes for standardize. Data where analyzed and further results are generated using software’s are; Minitab Version 17, Quality Companion Version 3, and Edraw-Max Version 7.